(untitled) (Lantanida Journal, 2022)
The use of local culture in the community can be used as a source of learning science in schools. This is one of the characteristics of the 2013 curriculum. However, the availability of local culture-oriented or ethnoscience-oriented chemistry books is not yet available in several schools in Pekalongan. This research aims to develop an ethnoscience-oriented chemical enrichment book by raising the typical food culture of Pekalongan. This research uses the Research and Development (R & D) method and the ADDIE (Analyze, Design, Development, Implement, and Evaluate) model. Data collection techniques use interviews, validation, and questionnaires. The results of data validation processing used the Guttman scale, and the response data used a Likert scale. This study produced an ethnoscience-oriented chemical enrichment book by raising the typical food culture of Pekalongan consisting of 5 special food items and 7 chemical materials and validation by 4 validators with a percentage of 100% from material experts and 93.33% from media experts. In addition, the responses of teachers and students of SMA Islam YMI and SMA PGRI 2 Kajen were obtained with an average percentage of 90.25% from teachers and 88.54% from students. Thus, this book is included in the very good category and is suitable for use as additional chemical teaching materials. Keywords: enrichment book; ethnoscience; typical Pekalongan food